The Effectiveness of Tontholo Cultural Practice on Increasing Breast Milk Production and Preventing Postpartum Depression - Yuliandary Yunus; Fatmah Zakaria; Nur Aprilia (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2026)
The postpartum period requires integrated physical and psychological care; however, interventions that simultaneously address breast milk production and postpartum depression through culturally grounded approaches remain limited. This study aimed to analyze the effectiveness of the Tontholo cultural practice in increasing breast milk production and preventing postpartum depression among postpartum mothers. A quasi-experimental study with a pretest–posttest control group design was conducted over one month involving 38 postpartum mothers selected using purposive sampling and divided into intervention (n=19) and control (n=19) groups; data were collected using breast milk production observation sheets and the Edinburgh Postnatal Depression Scale (EPDS) and analyzed using t-test with a significance level of p<0.05. The intervention group demonstrated a significantly greater increase in breast milk production compared to the control group. Moreover, a more substantial reduction in EPDS scores was observed in the intervention group, indicating improved maternal psychological well-being. In conclusion, Tontholo represents an innovative culture-based complementary model that integrates biological and psychosocial mechanisms to enhance lactation and reduce postpartum depression risk.